Rancangan Usulan Program Employee Engagement Menggunakan Pendekatan Design Thinking Pada Collega Group - Yunita Riski; Cecep Safa'atul Barkah (Institut Teknologi dan Sains Mandala, 2025)
The purpose of this study is to assess the condition of employee engagement and to offer employee engagement program recommendations to Collega Group. This study employed a mixed method with concurrent embedded research design and using a design thinking approach. Data sources included interviews, questionnaires, brainstorming sessions, and literature review. The stages of design thinking are followed while doing data analysis techniques on both qualitative and quantitative data. The study's findings indicate that, although 52.09% of Collega Group employees agree that they currently have employee engagement, there are still a number of issues that need to be resolved right away in order to maximize the conditions for employee engagement at Collega Group. These issues must be addressed in order to develop an employee engagement program using a design thinking approach. The issue that has to be resolved right away is making the most of division heads' position as leaders with the ability to oversee employee performance. The Micro Mentoring and One-on-One Meeting programs have been chosen as the programs to address these issues based on the difficulties identified.